2007
DOI: 10.1128/iai.00284-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Midgut and Salivary Glands as Specific and Distinct Barriers to Efficient Tick-Borne Transmission ofAnaplasma marginale

Abstract: Understanding the determinants of efficient tick-borne microbial transmission is needed to better predict the emergence of highly transmissible pathogen strains and disease outbreaks. Although the basic developmental cycle of Anaplasma and Ehrlichia spp. within the tick has been delineated, there are marked differences in the ability of specific strains to be efficiently tick transmitted. Using the highly transmissible St. Maries strain of Anaplasma marginale in Dermacentor andersoni as a positive control and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(128 citation statements)
references
References 30 publications
6
120
0
2
Order By: Relevance
“…(Uilenberg, 1995;De Waal et al, 2000;Jongejan and Uilenberg, 2004;Kocan et al, 2004). Tick transmissibility of Anaplasma is complex and ranges from very efficient transmission to non-transmission related to both Anaplasma strains as well as species of tick (Ueti et al, 2007). In Morocco, the vector competency of local tick species for transmitting A. marginale has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…(Uilenberg, 1995;De Waal et al, 2000;Jongejan and Uilenberg, 2004;Kocan et al, 2004). Tick transmissibility of Anaplasma is complex and ranges from very efficient transmission to non-transmission related to both Anaplasma strains as well as species of tick (Ueti et al, 2007). In Morocco, the vector competency of local tick species for transmitting A. marginale has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…While the A. marginale subsp. centrale vaccine strain was thought for a long time not to be transmitted by most ticks, it was shown that, in fact, it colonized the tick well but was not secreted into the tick saliva in sufficient quantities for robust transmission (23,24). Dramatically increasing tick numbers in transmission experiments overcame the transmission barrier (25).…”
Section: Discussionmentioning
confidence: 99%
“…The initial infection and a first round of intracellular replication occur within the tick midgut epithelium (7,9,10). The ability to enter and replicate in the midgut epithelium has been shown to be a determinant of A. marginale strain transmission fitness in the tick Dermacentor andersoni (16). Whether simultaneous acquisition of two A. marginale strains results in competition between the strains has not been tested, but entry of a first A. marginale strain into the midgut has been postulated to prevent establishment of infection by a second strain via a process termed "infection exclusion" (3).…”
mentioning
confidence: 99%